PHYSICOCHEMICAL, COMPLEX THERMAL, MICROSCOPIC AND RADIATION ANALYSIS OF DRY CONSTRUCTION MIXTURES WITH A NEW COMPOSITION - Mirzajanov Mamirjon Alimovich; Solijonov Hojiakbar Solijon ogli (Journals Park Publishing, 2025)
This article is devoted to the research carried out on the physicochemical, complex thermal, microscopic and radiation investigations of new-containing dry construction mixtures.